Why so few expert women in the water sector? Masculinity, race, sex, and policy narratives of technology, gender and development in Nepal - Liebrand, Janwillem (Frontiers in Human Dynamics, 2023)
To challenge the masculinity of the professional water sector, I take in this paper one of the core questions of feminist technology studies as the starting point: Why are there so few expert women in technology? By means of a critical feminist reading of policy and research documents, from the 1950s onwards, focusing on Nepal's history of rural development and technology transfer, I trace the origins of expert women's limited participation in politically relevant processes of water-decision making. The analysis reveals that both technology-anddevelopment -and women/gender-and-development policy narratives have validated, and continue to validate, women expert's subordinate position in the Nepali water sector. This is partially so, because donors and national governments insufficiently recognize the racial and sexist assumptions that are historically rooted into these policy narratives.